MicroRNA profiling in lymphocytes and serum of tyrosinemia type-I patients - KARATAŞ, ÖMER FARUK; Guzel, Esra; Karaca, Ender; Sevli, Serhat; Soyucen, Erdogan; Yuksel, Adnan; Ozen, Mustafa (My University, 2013)
Tyrosinemia type-I results from lack of fumarylacetoacetate hydrolase (FAH), which is a liver enzyme and also shown to be present in lymphocytes, fibroblasts, and cultured amniotic fluid cells. In young infants, symptoms of untreated Tyrosinemia type-I are restricted to severe liver involvement. Later in the first year; however, it is known to be present with liver and renal tubular dysfunction associated with growth failure and rickets. MicroRNAs are small regulatory RNAs that function post-transcriptionally. They target commonly 3--UTR of the mRNAs and inhibit protein expression by either blocking the synthesis or causing degradation of the mRNAs. MiRNA deregulation was observed in a variety of pathologic conditions but their roles in metabolic diseases were remained unsolved. We studied 6 patients with classical phenotypes of Tyrosinemia type-I. To identify possible miRNAs targeting FAH transcripts, microarray profiling of 961 miRNAs for lymphocytes and serum is performed. Computational algorithms are used for prediction of putative mRNA-miRNA interactions. A number of deregulated miRNAs, targeting the non-conserved sites on FAH transcripts were found. Besides, there are some miRNAs that are similarly altered both in lymphocytes and serum, possibly contributing to the disease phenotype. Since miRNAs may have an active role in the enzymatic pathway of tyrosine catabolism, characterizing miRNA profile in fibroblasts of tyrosinemia patients is also important because miRNAs would have distinctive role in disease pathogenesis and they are promising for future therapeutic studies.